Risk societies and environmental resilience: new villages, floods and abandonment along the Po river in the Middle Ages and the Early Modern Age (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
This paper intends to make a contribution to the debate on catastrophes and vulnerability of communities in history, starting from the analysis of the relationship between the floods of the Po and the abandonment of new villages between Lombardy and Piedmont. The socio‐economic analysis of settlements over the long term shows how the vulnerability of settlements increases, even more than due to social inequality, due to the loss of economic centrality.
Keywords: Risk societies; lost villages; floods; vulnerability; middle ages